The misogyny of iron deficiency. (7th March 2021) - Dugan, C.; MacLean, B.; Cabolis, K.; Abeysiri, S.; Khong, A.; Sajic, M.; Richards, T.; ,
Summary: Anaemia is common, particularly in women and the commonest underlying cause, iron deficiency, is often overlooked. Anaemia is associated with increased morbidity and mortality in patients undergoing anaesthesia; however, women are defined as being anaemic at a lower haemoglobin level than men. In this narrative review, we present the history of iron deficiency anaemia and how women's health has often been overlooked. Iron deficiency was first described as 'chlorosis' and a cause of 'hysteria' in women and initial treatment was by iron filings in cold wine. We present data of population screening demonstrating how common iron deficiency is, affecting 12–18% of apparently 'fit and healthy' women, with the most common cause being heavy menstrual bleeding; both conditions being often unrecognised. We describe a range of symptoms reported by women, that vary from fatigue to brain fog, hair loss and eating ice. We also describe experiments exploring the physical impact of iron deficiency, showing that reduced exercise performance is related to iron deficiency independent of haemoglobin concentration, as well as the impact of iron supplementation in women improving oxygen consumption and fitness. Overall, we demonstrate the need to single out women and investigate iron deficiency rather than accept the dogma of normality and differential treatment; this is to say, the need to change the current standard of care for women undergoing anaesthesia.